2018
DOI: 10.1055/s-0038-1655756
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Frailty on Postoperative Cardiopulmonary Complications in the Emergency General Surgery Population

Abstract: Background  The burden of frail patients undergoing emergency general surgery (EGS) is increasing rapidly and this population is particularly susceptible to postoperative cardiopulmonary complications and mortality. We aimed to determine the association between frailty, as defined by the previously described modified frailty index (mFI), and postoperative respiratory complications (unplanned reintubation, pneumonia, and prolonged ventilation), cardiac complications (myocardial infarction and cardiac arrest), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…[1][2][3] It was previously reported that a cross-reactive cephalosporin allergy occurs in 10% of penicillin-allergic patients. 4 This figure relates to studies prior to the 1980s, which demonstrated cross-reactivity between benzylpenicillin and first and second generation cephalosporins. However, early cephalosporin products may have been contaminated by Funding: None.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…[1][2][3] It was previously reported that a cross-reactive cephalosporin allergy occurs in 10% of penicillin-allergic patients. 4 This figure relates to studies prior to the 1980s, which demonstrated cross-reactivity between benzylpenicillin and first and second generation cephalosporins. However, early cephalosporin products may have been contaminated by Funding: None.…”
Section: Introductionmentioning
confidence: 93%
“…Frail patients have been found to have increased cardiopulmonary complications after emergency general surgery, increased mortality after major vascular surgery and increased mortality and decreased return to living at home after intensive care . Therefore, it seems likely that frailty would adversely affect recovery after in‐hospital cardiac arrest, but the association of frailty and outcome in this patient population has not previously been examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this acute setting, there is little time to medically optimize a patient with frailty before treatment. In single‐center studies within the United States, EGS patients with frailty experience a higher risk of in‐hospital complications, prolonged length of hospital and intensive care unit (ICU) stay, and 30‐day mortality . One prior study examined long‐term mortality among patients with frailty after EGS in Canada .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies identify frailty as an independent risk factor for major morbidity, mortality, protracted length of stay, and institutional discharge in elective surgical care, but also increasingly in acute surgical care (Tolstrup et al 2017;Saxton and Velanovich 2011;Kim et al 2014;Kenig et al 2015;Makary et al 2010;Hewitt et al 2015), though with limited studies focusing solely on emergency laparotomy patients (Hamidi et al 2018;Joseph et al 2016;Lorenzon et al 2017;Mogal et al 2017;Akyar et al 2018;Seib et al 2018).…”
Section: Introductionmentioning
confidence: 99%